2014
DOI: 10.2147/pgpm.s38117
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the homeobox transcription factor gene HOXB13: role in prostate cancer

Abstract: Prostate cancer (PC) is the most common noncutaneous cancer in men, and epidemiological studies suggest that about 40% of PC risk is heritable. Linkage analyses in hereditary PC families have identified multiple putative loci. However, until recently, identification of specific risk alleles has proven elusive. Cooney et al used linkage mapping and segregation analysis to identify a putative risk locus on chromosome 17q21-22. In search of causative variant(s) in genes from the candidate region, a novel, potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The most commonly observed mutation is the substitution of glycine at amino acid residue 84 to glutamic acid (G84E), but the mechanism by which the mutation confers risk has not yet been determined [ 34 , 35 ]. HOXB13 promotes or represses prostate cancer cell proliferation depending on the cellular context, such as with androgen receptor expression [ 36 ]. HOXB13 has opposing functions in other cancers as well.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly observed mutation is the substitution of glycine at amino acid residue 84 to glutamic acid (G84E), but the mechanism by which the mutation confers risk has not yet been determined [ 34 , 35 ]. HOXB13 promotes or represses prostate cancer cell proliferation depending on the cellular context, such as with androgen receptor expression [ 36 ]. HOXB13 has opposing functions in other cancers as well.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike for FOXA1, no somatic mutations in HOXB13 have been detected in primary prostate cancer or in the metastatic disease. However, a recurrent germline mutation HOXB13 (G84E) has been identified (Ewing et al 2012), which is associated with increased prostate cancer risk (Decker & Ostrander 2014). Recently, more hereditary HOXB13 mutations conferring increased risk of prostate cancer have been reported (Maia et al 2015).…”
Section: Hoxb13mentioning
confidence: 99%
“…The homeobox B13 ( HOXB13 ) gene is involved in prostate development [1], and in vitro results have suggested that its transcription factor is involved in prostate cancer (PCa) cell growth through androgen receptor interaction, regulation by FOXA1 , and other pathways [2]. The HOXB13 missense mutation G84E is a founder mutation in Nordic populations [3], with reported carrier frequencies of 0.2–1.4% [4], [5], [6], [7], and is carried by 0.1–0.5% in other Western European populations [4], [8].…”
Section: Introductionmentioning
confidence: 99%